2022
DOI: 10.1016/j.medcli.2021.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-dose intravenous vitamin C on prognosis in patients with SARS-CoV-2 pneumonia

Abstract: Antecedentes: Hasta ahora, la pandemia de la enfermedad por coronavirus 2019 (COVID-19) ha afectado a más de 2,5 millones de individuos en todo el mundo, con aproximadamente 170.000 muertes. En la actualidad, no existen tratamientos con evidencias sólidas de beneficio clínico, y la utilización de agentes experimentales ha sido recomendada por las guías nacionales e internacionales como parte de los estudios clínicos. Método: En este estudio retrospectivo se incluyeron un total de 323 pacientes con s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…The duration of treatment varied from four to 18 days. There was a low risk of bias for seven studies [8,11,14,21,22,24,25], while the risk of bias for two studies was high [13,20], as shown in Supplementary Table 2.…”
Section: Vitamin C Supplementationmentioning
confidence: 95%
See 2 more Smart Citations
“…The duration of treatment varied from four to 18 days. There was a low risk of bias for seven studies [8,11,14,21,22,24,25], while the risk of bias for two studies was high [13,20], as shown in Supplementary Table 2.…”
Section: Vitamin C Supplementationmentioning
confidence: 95%
“…The mean age was 61.0 ± 15.02, and 57.4% were males. These studies were conducted in China [8,14,22], Iran [13], Pakistan [20], Saudi Arabia [24], Turkey [25], and United States [11,21]. The studies provided daily doses alone [11,13,14,20e22,24,25] or daily doses after a loading dose [8].…”
Section: Vitamin C Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few observational research and preliminary clinical studies on vitamin C in patients with COVID-19 corroborate their findings by noting a reduction in hyper inflammation (43,44,47), improvement in the oxygen support status (39,41,46,47), lower incidence of thrombosis (42), and also the reduced disease aggravation in the early stage of COVID-19 pneumonia (43), the mortality rate is still controversial among the studies. Some authors found a reduction in mortality (46) whereas other studies with vitamin C did not observe a difference in mortality when compared to patients in the control group (40,42,45). Controversial research with vitamin C also demonstrated failure to ameliorate the mechanical ventilation of patients with COVID-19 (39,40) and did not find a substantial decrease in the duration of symptoms (37).…”
Section: Vitamin Cmentioning
confidence: 99%
“…Among 108 coronavirus-associated melatonin articles extracted and assessed for eligibility, three studies with a melatonin approach were included (33)(34)(35). Moreover, among the 399 coronavirus-associated zinc studies extracted and evaluated for eligibility, three studies entered the inclusion criteria (36)(37)(38), whereas among 344 coronavirus-associated vitamin C (or ascorbic acid) papers initially extracted and analyzed for eligibility, a total of 10 papers were also included as RCTs or observational research (37,(39)(40)(41)(42)(43)(44)(45)(46)(47).…”
Section: Characterization Of Included Studiesmentioning
confidence: 99%